Multi population traditional Evolutionary Programming approach for Distributed Generation / Mohd Nazmi Adnan - Adnan, Mohd Nazmi (2009)
This thesis presents, the study involves in the development of multi population Evolutionary Programming for Distributed Generation (DG) installation in distribution systems. While installing the DG into the system, improve on the voltage profile and reduction of power loss based on the optimal location and sizing of DG. Generally, DG is defined as a small-scale electricity generation which the electricity is generated in large power stations to achieve cost reduction.